The Solodamu Surveys: determining fossil fuel use and sea transport need in a coastal village in Fiji - Newell, Alison P.; Bola, Amelia (Frontiers in Marine Science, 2015)
Domestic sea transport is critical to all aspects of life in the Pacific, providing access to markets and health and education services, as well as enabling cultural and social connectivity. Current sea transport services are entirely dependent upon use of increasingly expensive fossil fuels. Whilst there has been increasing research on international shipping, very little focus has been given to date to domestic shipping in the Pacific, and in particular at the local, village level. Recent studies have highlighted lack of data, particularly at a village level, as being a major impediment to progressing a shift to more sustainable transport. The importance of transport in achieving sustainable development and “green growth” is being increasingly highlighted by Pacific Leaders as a key priority, and particularly the need to find alternatives to reduce the region’s crippling dependency on imported fossil fuels. Small Island Developing States (SIDS) in other regions also face similar challenges. This paper provides a summary of the findings of a village-based assessment of transport and fossil fuel use in Solodamu Village, Kadavu, Fiji carried out in 2009 and 2011. The objectives of the surveys were to gauge the overall sea, land and air transport use by the village and the fossil fuel footprint of the village by collecting data on a household by household basis. We then go on to outline how this assessment methodology has been expanded for an island group and highlight the potential of using this in other SIDS, so building the data sets available for more accurate analysis of both transport need and fossil fuel use to better address the issues of fossil fuel dependency and sustainable transport for the Pacific.